Application of Adaptive Gamification to Enhance Student Engagement in Inclusive Science Learning - Suyantiningsih Suyantiningsih; Santi Herawati (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study aimed to improve student engagement and learning outcomes of students with special educational needs in ecosystem learning through adaptive gamification based on the Octalysis Framework. The study employed a Classroom Action Research (CAR) design conducted in three cycles, consisting of planning, action, observation, and reflection. The participants were three seventh-grade students with special educational needs at SMP Negeri 4 Kombeng. Data were collected through student engagement observation sheets, learning achievement tests, field notes, and documentation, and were analyzed using descriptive quantitative and qualitative approaches. The results indicated consistent improvements across the three cycles. The mean student engagement score increased from 2.11 in Cycle I to 3.15 in Cycle II and 3.59 in Cycle III. The mean learning outcome also improved from 60.00 to 75.33 and 83.00, while the classical learning mastery increased from 33.33% in Cycle I to 66.67% in Cycle II and remained stable in Cycle III. Classroom observations further revealed increased motivation, participation, confidence, and active involvement throughout the learning process. These findings demonstrate that adaptive gamification based on the Octalysis Framework provides a more engaging, personalized, and inclusive learning experience, thereby enhancing both student engagement and learning outcomes in science education for students with special educational needs.